Adding Clonidine to Ropivacaine in Brachial Plexus Block for Upper Limb Surgeries: Study of Hemodynamic Variables - Dr Virupakshamma; Ajay Basarigidad (Academia Anesthesiologica International, 2019)
Background: Ropivacaine is a long acting amide local anaesthetic agent. It was first synthesized in 1957 along with bupivacaine and mepivacaine. It is a pure S-enantiomer while bupivacaine is a racemic mixture. Ropivacaine causes reversible inhibition of sodium ion influx, and thereby blocks impulse conduction in nerve fibres. This action is potentiated by dose-dependent inhibition of potassium channels. Subjects and Methods: This study was conducted on 60 patients undergoing upper limb surgeries aged between 18 to 55 years under supraclavicular block. Informed written consent was taken. Result values were recorded using a preset proforma. Results: There were 24 patients in Group R and 23 patients in Group RC belonging to ASA Grade I, and 6 patients in Group R and 7 patients in Group RC belonging to ASA Grade II which was considered statistically not significant. Conclusion: The combination produces improved analgesia, resulting in a prolonged effect and stable hemodynamics.